Nasal septal teratoma in a child - Ibekwe, Titus S (BioMed Central, 2007)
BACKGROUND: Teratoma is a rare developmental neoplasm that arises from totipotential tumor stem cells. Head and neck teratomas constitute about 10% of all cases. Only two cases of mature teratoma of the nasal septum have previously been documented in the world literature. CASE PRESENTATION: We present a case of histologically confirmed mature teratoma arising from the nasal septum in an eighteen month old Nigerian female who presented with a history of noisy breathing associated with recurrent rhinorrhea since birth. Physical examination revealed obstruction of the right nasal cavity by a pale fleshy mass. She underwent a total surgical excision and to date, after thirty one months follow-up, she is free from recurrence. CONCLUSION: The prognosis for benign teratoma of the nasal septum is good following total surgical excision.